2021
DOI: 10.1097/shk.0000000000001896
|View full text |Cite
|
Sign up to set email alerts
|

Renal Resistive Index on Intensive Care Unit Admission Correlates With Tissue Hypoperfusion Indices and Predicts Clinical Outcome

Abstract: Background: Recent advancements in the context of shock pathophysiology, support ultrasound assessment of organ perfusion. Renal resistive index (RRI) has been used to evaluate renal blood ow.Our aim was to investigate the relation between RRI, and global tissue hypoperfusion indices, in mechanically ventilated critically ill patients and their association with clinical outcome. Methods: In this prospective observational study, RRI was measured within 24 hours of intensive care unit (ICU) admission. Clinical a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The RRI was routinely determined in all CS patients as an established indicator for the occurrence and reversibility of acute kidney injury (AKI) [ 17 20 ]. RRI was determined by intrarenal artery Doppler measurements (peak systolic velocity minus the end-diastolic velocity divided by the peak systolic velocity).…”
Section: Methodsmentioning
confidence: 99%
“…The RRI was routinely determined in all CS patients as an established indicator for the occurrence and reversibility of acute kidney injury (AKI) [ 17 20 ]. RRI was determined by intrarenal artery Doppler measurements (peak systolic velocity minus the end-diastolic velocity divided by the peak systolic velocity).…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, fluid accumulation has been demonstrated to be a negative predictor for the recovery of kidney function because it may cause hypoxemic injury to the kidney [ 20 ]. Furthermore, as a systemic perfusion indicator, lactate, can reflect kidney hypoperfusion to some extent [ 21 ], which may have an impact on the reversibility of AKI. Some studies have shown that the severity of illness may also help to predict kidney recovery from AKI [ 1 , 22 ].…”
Section: Introductionmentioning
confidence: 99%